The Use of Video as a Media to Improve Students’ Vocabulary Mastery - Yeni Mardiyana Devanti (Universitas Muhammadiyah Jember, 2018)
The objective of this Classroom Action Research was to improve students’vocabulary mastery by using video as a media in teaching and learning process.It covered four stages of activities, they were planning, implementing, observing,and reflecting of the action. The subject of this research was class VII C of SMPMuhammadiyah 1 Jember. In this research, the primary data were collectedfrom the vocabulary test while the observation check list as supporting data was taking during the teaching and learning process. Video as a media of teaching and learning vocabulary improved students vocabualry mastery in two cyclesfrom the percentage of students scored ≥ 70,was 69% in cycle 1 to 80% in cycle2, it also improved students’ active participation from 55% in cycle 1 to 77%at the end of the cycle 2. Based on the research result, it can be concluded thatthe video as a media of teaching English vocabulary was able to improve theseventh grade students’ vocabulary mastery and students’s active participation.